(untitled) (Confluenţe Bibliologice, 2025)
Antonio Magliabechi, famous Florence’s librarian, in his private life was very eccentric. By the other hand he became the central ﬁgure of literary life in Florence. Antonio’s memory was miraculous. Magliabechi knew not only all the volumes in his own library or in Cosimo III de’ Medici’s private library, but could also tell the page and paragraph in which any passage occurred. Scholarships corresponded with him. Magliabechi was ready to give a friendly answer to questions. So, he was an unacknowledged collaborator on many publications.